The Concept Of Tawāzun In Hamka's Tafsir Al-Azhar And Its Relevance To The Phenomenon Of Hustle Culture - Baso Muh Wahidin; Ahmad Nurrohim; Zulfikar Zulfikar (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The rise of hustle culture in the digital era has encouraged a materialistic orientation of life and limitless productivity, resulting in widespread anxiety, mental exhaustion, and spiritual disorientation. This study aims to examine the concept of Tawāzun in Buya Hamka’s Tafsir Al-Azhar and analyze its relevance as a paradigm of balanced living within contemporary work culture. The research employs a qualitative descriptive-analytical approach using the thematic interpretation (maudhū‘ī) method. The primary source is the Singapore edition of Tafsir Al-Azhar in ten volumes published by Pustaka Nasional Pte Ltd, with thematic analysis focused on QS. Al-Qashash: 77, QS. Al-Baqarah: 201, QS. Al-Jumu‘ah: 10, and QS. At-Takātsur: 1–2. The findings reveal that Hamka conceptualizes Tawāzun not merely as time allocation between worldly and spiritual affairs, but as an integrated orientation of work, spirituality, and human purpose grounded in tawhid. This article formulates the concept of al-niyyah al-mutawāzinah as an analytical construct that positions work as an act of worship and meaningful existence. The concept offers a critical response to hustle culture while presenting an ontological, teleological, and psychological framework of balanced living.